N-acetylated sugars in clownfish and damselfish skin mucus as messengers involved in chemical recognition by anemone host - Sara Heim; Tony Teav; Fabio Cortesi; Hector Gallart-Ayala; Julijana Ivanisevic; Nicolas Salamin (Scientific Reports)
Abstract The clownfish - sea anemone system is a great example of symbiotic mutualism where host «toxicity» does not impact its symbiont partner, although the underlying protection mechanism remains unclear. The regulation of nematocyst discharge in cnidarians involves N-acetylated sugars like sialic acid, that bind chemoreceptors on the tentacles of sea anemones, leading to the release of stings. It has been suggested that clownfish could be deprived of sialic acid on their skin surface, sparing them from being stung and facilitating mutualism with sea anemones. In this study, we sampled the skin mucus of two anemone symbionts, the clownfish Amphiprion akindynos and the juvenile damselfish Dascyllus trimaculatus, as well as two non-symbiotic adult damselfish Pomacentrus moluccensis and P. pavo. The free and total sialic acid content, including its conjugated form, and three other intermediates of this pathway were quantified using a stable isotope dilution mass spectrometry approach. We found significantly higher levels of sialic acid and its precursor in the non-symbiotic damselfishes. Concentrations of total sialic acid in anemone symbionts ranged between 13 µM and 16 µM, whereas the non-symbiotic damselfishes ranged between 21 µM and 30 µM. The presence of this metabolite and its precursors, as triggers of nematocyst discharge, in anemone symbionts, suggests that this is not the direct mechanism of protection or that the trigger is concentration dependent. This experiment demonstrates that anemone symbionts are not spared by nematocysts because of a lack of N-acetylated sugars, as previously thought, rather the biochemical mechanisms involving N-acetylated sugars are more complex than just a presence/absence of these molecules.